Effects of Maceral Compositions of Coal on Methane Adsorption Heat - Yingke Liu; Jianhong Kang; Fubao Zhou; Yanming Fan; Haijian Li (Geofluids)
The role of maceral compositions (vitrinite and inertinite) in the adsorption characteristics of coal has not been fully understood in terms of energy. In this study, using a microcalorimeter, the adsorption heat of maceral compositions for methane is directly measured for five groups of Chinese coal samples with different coal ranks. The results show that the adsorption heat of the maceral concentrates varies with increasing coal rank, but for the same coal sample, the vitrinite concentrates have a higher adsorption heat than the inertinite concentrates. Furthermore, the adsorption heat of both vitrinite and inertinite concentrates is highest at the long-flame coal stage. This finding indicates that the coalification and maceral compositions have significant effects on the adsorption heat of coal for methane. It is observed that although the inertinite concentrates have a larger pore volume, they are less microporous than their rank equivalent vitrinite concentrates, resulting in lower adsorption heat. Furthermore, it is revealed that the adsorption heat of both vitrinite and inertinite concentrates is primarily correlated to the content of oxygen-containing functional groups and aliphatic hydrocarbons.